Extracellular matrix in plants and animals: hooks and locks for viruses - Stavolone, L.; Lionetti, V. (Frontiers Media, 2017)
The extracellular matrix (ECM) of animal and plants cells plays important roles in viral diseases. While in animal cells extracellular matrix components can be exploited by viruses for recognition, attachment and entry, the plant cell wall acts as a physical barrier to viral entry and adds a higher level of difficulty to intercellular movement of viruses. Interestingly, both in plant and animal systems, ECM can be strongly remodeled during virus infection, and the understanding of remodeling mechanisms and molecular players offers new perspectives for therapeutic intervention. This review focuses on the different roles played by the ECM in plant and animal hosts during virus infection with special emphasis on the similarities and differences. Possible biotechnological applications aimed at improving viral resistance are discussed.